UAS Regulations in The Aspect of Unmanned Aviation Safety - Wiktor Wyszywacz (Przegląd Komunikacyjny)
Abstract: The dynamic development of unmanned aviation forced the definition of the rules for performing UAS flight operations. The UAS regulations set the rules for the use of unmanned aerial vehicles and organize their functioning in integration with manned aviation. The paramount goal of the introduced regulations and provisions is to ensure an appropriate level of safety. Regulations should take into account both the current development needs of the industry and clearly defined safety objectives. It is important to all aviation stakeholders that, despite the shared use of a part of the airspace by both types of aviation, public recognition of the high level of aviation safety has not deteriorated. The introduced regulations had a direct impact on the safety of operations in both manned and unmanned aviation. The current experience of the impact of regulations in manned aviation is outlined and the current regulations in unmanned aviation, as well as safety and risk management, are discussed. The importance of the VLOS and BVLOS unmanned operations as well as the open, special and certified categories were discussed. In both types of aviation, one of the most significant factors influencing the level of safety is the human factor (HF). Therefore, the participation and importance of HF as an important component of the existing and implemented regulations was taken into account. Reference was made to the changes currently introduced at the national and European levels. The final conclusions are presented in the summary. Keywords: UAS; Safety; Threats; Risk; Regulations; Safety management; SORA